Potential, spatial distribution and economic performance of regional biomass chains: The North of the Netherlands as example - van der Hilst, Floor; Dornburg, Veronika; Sanders, Johan P. M.; Elbersen, Berien S.; Graves, Anil; Turkenburg, Wim C.; Elbersen, H. Wolter; van Dam, Jinke M. C.; Faaij, André P. C. (Elsevier, 2010)
This work assesses the viability of regional biomass chains by comparing the economic performance of potential bioenergy crops with the performance of current agricultural land uses. The biomass chains assessed are ethanol production from Miscanthus and from sugar beet in the North of the Netherlands. The competitiveness of bioenergy crops is assessed by comparing the Net Present Value (NPV) of perennial crops, current rotations, and rotation schemes which include additional years of sugar beet. The current land use and soil suitability for present and bioenergy crops are mapped using a geographical information system (GIS) and the spatial distribution of economic profitability is used to indicate where land use change is most likely to occur. Bioethanol production costs are then compared with petrol costs. The productions costs comprise costs associated with cultivation, harvest, transport and conversion to ethanol. The NPVs and cost of feedstock production are calculated for seven soil suitability classes. The results show that bioenergy crops are not competitive with current cropping systems on soils classed as “suitable”. On less suitable soils, the return on intensively managed crops is low and perennial crops achieve better NPVs than common rotations. Our results showed that minimum feedstock production costs are 5.4 €/GJ for Miscanthus and 9.7 €/GJ for sugar beet depending on soil suitability. Ethanol from Miscanthus (24 €/GJ) is a better option than ethanol from sugar beet (27 €/GJ) in terms of costs. The cost of bioethanol production from domestically cultivated crops is not competitive with petrol (12.34€/GJ) production under current circumstances. We propose that the method demonstrated in this study provides a generic approach for identifying viable locations for bioenergy crop production based on soil properties and cur